Novel landscapes. A new kind of wilderness for damaged peatlands on the Isle of Skye in Scotland - Lobosco, Gianni (2020)
ABSTRACT: The essay discusses the theoretical implications of ecological restoration in landscape architecture. The study presents a management plan for highly damaged peatlands in the Isle of Skye in Scotland, where the habitat is threatened by a radical forestation process. Being a natural carbon stock, damaged peatlands are a major source of greenhouse gas emissions. The project suggests gradually turning the case-study area's economy from tree farming to tourism, making the most out of the unique biodiversity of peatlands. The proposal traces a chronological activation plan of a touristic network that will run in parallel with the restoration of peats, native broadleaf forests, heather and cotion-grass meadows. Depending on the ability to recover of different soils, the restoration plan intends to gradually activate new dynamics in the landscape. The result is a stable “novel ecosystem” whose key interactions and processes are induced by new biotic and abiotic conditions. The article investigates and discusses possible strategies to develop a new kind of wilderness that differs from any previous condition and emerges from an alternative land use.